Matrices secreted during simultaneous osteogenesis and adipogenesis of mesenchymal stem cells affect stem cells differentiation. (15th April 2016) - Cai, Rong; Nakamoto, Tomoko; Hoshiba, Takashi; Kawazoe, Naoki; Chen, Guoping
Graphical abstract: Abstract: The extracellular matrix (ECM) plays a pivotal role in regulating stem cell functions. The ECM dynamically changes during tissue development. It remains a great challenge to mimic the dynamically changing ECM. In this study, we prepared novel types of extracellular matrices that could mimic the dynamic variation of extracellular matrices, which were derived from simultaneous osteogenesis and adipogenesis of human bone marrow-derived mesenchymal stem cells (MSCs). Four ECMs simultaneously mimicking early osteogenesis and early adipogenesis (EOEA), early osteogenesis and late adipogenesis (EOLA), late osteogenesis and early adipogenesis (LOEA), late osteogenesis and late adipogenesis (LOLA) were prepared. The stepwise osteogenesis–co-adipogenesis-mimicking matrices had different compositions and different effects on the osteogenic and adipogenic differentiation of MSCs. The matrices could provide very useful tools to investigate the interaction between ECM and stem cells and the role of ECM on stem cell differentiation. Statement of Significance: Extracellular matrices (ECMs) are dynamically remodeled to regulate stem cell functions during tissue development. Until now, mimicking the ECM variation during stem cell differentiation to single cell type has been reported. However, there is no report on simultaneous mimicking of stem cell differentiation to two types of cells. In this study, we prepared the mixture ECMs derived from simultaneous osteogenesis and adipogenesis of MSCs at different stages and found that they could regulate stem cell differentiation. The concept is new and the ECMs are novel. No such ECMs have been reported previously. The matrices will provide very useful tools to investigate the interaction between ECM and stem cells and the role of ECM on stem cell differentiation.